2006
DOI: 10.1007/s10286-006-0308-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of C-peptide on gastric emptying in longstanding type 1 diabetes

Abstract: Gastric emptying (GE) of a solid (100 g beef) and liquid (150 ml 10 % dextrose) meal was measured in eight patients with type 1 diabetes during intravenous infusion of C-peptide (6 pmol/kg/ min) or isotonic saline. C-peptide had no effect on either solid or liquid GE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This effect was also observed for the magnitude of small intestinal glucose disposal. 71 Additionally, a number of studies have reported that although GIP is the major contributor to the incretin effect when the rate of gastric emptying is ≤2 kcal/min, the effects of GLP-1 are dominant when the rate of gastric emptying is ≥3 kcal/min. 40,41,63,64 Effect of glycaemia on gastric emptying Alterations in glycaemia can induce reversible changes in the rate of gastric emptying.…”
Section: Gastric Emptying and Glycaemiamentioning
confidence: 99%
“…This effect was also observed for the magnitude of small intestinal glucose disposal. 71 Additionally, a number of studies have reported that although GIP is the major contributor to the incretin effect when the rate of gastric emptying is ≤2 kcal/min, the effects of GLP-1 are dominant when the rate of gastric emptying is ≥3 kcal/min. 40,41,63,64 Effect of glycaemia on gastric emptying Alterations in glycaemia can induce reversible changes in the rate of gastric emptying.…”
Section: Gastric Emptying and Glycaemiamentioning
confidence: 99%
“…Cholecystokinin antagonists are also being developed [32]. Acute administration of C-peptide had no effect on gastric emptying in a small cohort of patients with type 1 diabetes [47]. Agents that modulate sensation (5HT 3 antagonists, κ-opiate agonists) or promote relaxation of the stomach have thus far been disappointing [4].…”
Section: Stomachmentioning
confidence: 98%